Chemical Neurolysis of the Inferior Hypogastric Plexus for the Treatment of Cancer-Related Pelvic and Perineal Pain - Sahar Abd-Elbaky Mohamed; Doaa Gomaa Ahmed; Mohamad Farouk Mohamad (Pain Research and Management)
BACKGROUND: Various interventions, including the superior hypogastric plexus block and ganglion impar block, are commonly used for the treatment of pelvic or perineal pain caused by cancer. The inferior hypogastric plexus block (performed using a trans-sacral approach under fluoroscopy and using a local anesthetics/steroid combination) for the diagnosis and treatment of chronic pain conditions involving the lower pelvic viscera was first described in 2007. Neurolysis of the inferior hypogastric plexus may be useful for the treatment of pelvic and perineal pain caused by cancer.